Production of mouse immunoglobulin G by a hybrid plant derived from tobacco-mouse cell fusions - Makonkawkeyoon S. (2014)
Mouse-tobacco hybrid calli, and complete plants producing mouse gamma-3 heavy and lambda light chains, have been generated by somatic cell fusions of mouse spleen cells and tobacco mesophyll protoplasts. Both gamma 3 and lambda chains were detected in hybrid calli and complete plants by enzyme-linked immunosorbent assay, immunofluorescent staining, and Western blotting. When cellular DNA from hybrid tobacco mesophyll protoplasts was amplified by the polymerase chain reaction (PCR) using two pairs of gamma 3 chain DNA primers and one pair of lambda chain DNA primers, the PCR products contained gamma 3 and lambda chain DNAs, which could be detected by southern blotting and DNA hybridization, using specific synthetic oligonucleotide probes for gamma 3 and lambda respectively. In situ hybridization of hybrid tobacco mesophyll protoplasts with specific recombinant DNA probes of gamma 3 and lambda chains showed the presence of gamma 3 and lambda chain DNAs in the hybrid protoplasts.